Cover Cracking of Reinforced Concrete Beams Due to Corrosion of Steel - Ahmed, Shaikh; Maalej, M.; Mihashi, H. (American Concrete Institute, 2007)
A finite element (FE) model is proposed to simulate the corrosion-induced cracking of reinforced concrete (RC) beams. The smeared cracking approach is used to model the cracking ofordinary concrete, ductile fiber-reinforced cementitious composites (DFRCC), and engineered cementitious composites (ECC). The model simulates the cracking of ordinary concrete beams and RCbeams containing ECC and DFRCC materials. The strains obtained from the FE models are compared with that measured by the fiber-optic strain sensor (FOSS) gauge, which is placed between longitudinal steel bars at midspan of RC beams during the accelerated corrosion test. The model could predict thecorrosion-induced damage tolerance of ECC and DFRCC materials and found that it is several times higher than that of ordinary concrete. The model predicted the uniform damage in the ECC and the DFRCC materials due to corrosion compared with localized damage in ordinary concrete. The model also predicted that the delamination of the cover of the RC beams containing ECC/DFRCC materials will occur at a higher level of steel loss compared with that of an ordinary concrete beam. The betterperformance exhibited by the RC beam containing ECC/DFRCC materials is due to their higher tensile strain capacity, strain hardening, and multiple cracking behavior.